Enhancing Salt Tolerance in Oryza sativa through Plant Growth-Promoting Rhizobacteria via Preferential Upregulation of Plant Salt-Responsive Genes (Plant Tissue Culture and Biotechnology, 2026)
Global climate change poses a major threat to food security by reducing crop productivity, particularly through soil salinization. Plant growth-promoting rhizobacteria (PGPR) offer a climate-smart and sustainable solution to mitigate salinity stress and enhance crop yield. This study investigated four potent endophytic PGPR: Enterobacter cloacae, Achromobacter xylosoxidans, Bacillus aryabhattai, and Stenotrophomonas pavanii, previously isolated from rice endophytes grown in coastal agricultural lands of Bangladesh. These strains were screened for plant growth-promoting traits and tested on the salt-sensitive rice cultivar BRRI-28 under 200 mM NaCl stress. PGPR-treated plants exhibited higher chlorophyll, carbohydrate, and protein levels, along with increased proline accumulation, indicating improved photosynthetic and metabolic activity. Reduced malondialdehyde (MDA) levels indicated enhanced membrane stability. Gene expression analysis revealed upregulation of salt-tolerance genes (GIG, BZ8, SOS1), while eEF-1α expression remained stable. These findings demonstrate that PGPR-mediated enhancement of salt tolerance in Oryza sativa is associated with the upregulation of key salt-responsive genes, consistent with a targeted plant–microbe interaction that may contribute to improved salinity tolerance.Plant Tissue Cult. & Biotech. 36(1): 91-105, 2026 (June)